(1) \( \frac{3^{x} \times 3^{-3}}{9^{x}}=1 \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
To solve the equation \( \frac{3^{x} \times 3^{-3}}{9^{x}}=1 \), we can first express \( 9^{x} \) in terms of base 3. Since \( 9 = 3^{2} \), we have \( 9^{x} = (3^{2})^{x} = 3^{2x} \). Now substitute this into the equation: \[ \frac{3^{x} \times 3^{-3}}{3^{2x}}=1 \] This simplifies to: \[ \frac{3^{x - 3}}{3^{2x}} = 1 \] Using the properties of exponents, we can combine the bases: \[ 3^{x - 3 - 2x} = 1 \] This further simplifies to: \[ 3^{-x - 3} = 1 \] Since \( 3^{0} = 1 \), we can set the exponent equal to 0: \[ -x - 3 = 0 \] Solving for \( x \), we get: \[ -x = 3 \quad \Rightarrow \quad x = -3 \] So the solution is \( x = -3 \).